Clinical outcomes of 11,436 kidney transplants performed in a single center - Hospital do Rim - Pestana,José Medina (2017)
Abstract Introduction: Kidney transplantation is considered a cost-effective treatment compared to dialysis but accounts for a significant percentage of the public health care resources. Therefore, efficient systems capable of performing high number of procedures are attractive and sustainable. Objective: The aim of this study was to evaluate clinical outcomes of 11,436 kidney transplants regularly performed in a single transplant dedicated center over the last 18 years. Methods: This was a retrospective study performed in a single specialized transplant center. All consecutive patients who underwent transplantation between 08/18/1998 and 12/31/2015 were included in the analysis. Results: The annual number of transplants increased from 394 in 1999 to 886 in 2015, with a progressive reduction in the proportion of living donor kidney transplants (70% vs. 23%) and yielding over 8869 patients in regular follow up. Of 11,707 kidney transplants performed, 5348 (45.7%) were from living, 3614 (30.9%) standard and 1618 (13.8%) expanded criteria deceased donors, 856 (7.3%) pediatric and 271 (2.3%) simultaneous kidney-pancreas transplants. Comparing 1998-2002 and 2011-2014, five-years graft survival increased for kidney transplants performed with living donors (83.3% vs. 93.1%, p < 0.001), standard deceased donors (60.7% vs. 79.7%, p < 0.001), expanded criteria donors (46.5% vs. 71.5%, p < 0.001) and for the pediatric population (79.8% vs. 80.9%, p = 0.684). Conclusion: The implementation of a dynamic and efficacious health care system was associated with a progressive increase in the number of kidney transplants, in the cumulative number of patients in follow up and a shift from living related to deceased donor kidney transplants, with associated progressive increase in patient and graft survivals.